2014
DOI: 10.18632/oncotarget.1677
|View full text |Cite
|
Sign up to set email alerts
|

KIAA1114, a full-length protein encoded by the trophinin gene, is a novel surface marker for isolating tumor-initiating cells of multiple hepatocellular carcinoma subtypes

Abstract: Identification of novel biomarkers for tumor-initiating cells (TICs) is of critical importance for developing diagnostic and therapeutic strategies against cancers. Here we identified the role of KIAA1114, a full-length translational product of the trophinin gene, as a distinctive marker for TICs in human liver cancer by developing a DNA vaccine-induced monoclonal antibody targeting the putative extracellular domain of KIAA1114. Compared with other established markers of liver TICs, KIAA1114 was unique in that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…It was reported that AFP, KIF18A and KIAA1114 are biological markers correlated with HCC [30, 31], and AFP is widely used in clinical. The re-expression of AFP in most HCC patients has been studied for decades.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that AFP, KIF18A and KIAA1114 are biological markers correlated with HCC [30, 31], and AFP is widely used in clinical. The re-expression of AFP in most HCC patients has been studied for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Trophinin is one of three membrane proteins derived from the TRO gene (also known as MAGE-D3) (Kim et al, 2014) and mediates Ca 2+ -independent homophilic cell adhesion in synergy with its cytoplasmic partners tastin (also known as TROAP), bystin and ErbB4 (Fukuda and Sugihara, 2012;see poster). Binding of trophinin from an adjacent cell is predicted to dissociate bystin, thereby permitting phosphorylation of ErbB4 when heparin-binding epidermal-like growth factor (HB-EGF) is bound to ErbB4 (Sugihara et al, 2007).…”
Section: Trophinin and Hb-egfmentioning
confidence: 99%
“…The comparison among MCMs in HCC has not yet been performed. Hepatocarcinogenesis is a typical multistage process characterized by chronic viral infection, cirrhosis, and HCC [ 28 , 29 ]. Here, we feature the expression dynamics of MCM2, MCM3, MCM4, MCM5, MCM6, MCM7, MCM8, MCM9, MCM10 and RecQ like helicase 4 (RECQL4) in the typical multistep of hepatocarcinogenesis and demonstrate the association between MCMs and clinicopathological characteristics, diagnosis and prognosis in HCC patients.…”
Section: Introductionmentioning
confidence: 99%